Exploring the environmental sustainability capabilities and resource management strategies of German third-party logistics providers (3PL) - Balint, Martin; Vilas-Boas, J.; Möhring, Monika (Proceedings of 27th EurOMA, 2020)
This paper addresses a gap in knowledge and practice by presenting a qualitative assessment of environmental sustainability and resource management capabilities at three German 3PL companies. The inquiry focuses on the link between resource possession and exploitation and the environmental-competitive advantage link by drawing on assumptions of the natural-resource-based-view of the firm. The findings underpin those capabilities that allow the minimisation of pollution and waste are expected to help 3PL companies to achieve a differentiation advantage and to lower operating costs. They also indicate that bundled capabilities need to be leveraged in order to become a source of competitive advantage.